2018
DOI: 10.15294/jpii.v7i4.16089
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Scientific Independence towards Students’ Content Analysis and Science Process Skills on Cell Metabolism Topic

Abstract: Students commonly judge that cell metabolism topic is arduous since they only listen to their teacher and memorizing concept without a deep comprehension. Other than that, a direct explanation could not enhance the students' science process skills. Thus, this research intended to analyze the differences of the content-analysis and science process skills between the students experiencing a learning that oriented to scientific independence (experimental class) and those joining a direct learning (control class).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…It is supposed to help us to determine the right relations between different values of science and to understand that science is not an isolated thing, but a totality which is not just a sum of its parts. (Ekawati et al, 2018) The students' content analysis and science process skills of the experimental group (scien¬tific independence-based learning with inquiry model) and control group (direct learning model) differed quite remarkably. Broszkiewicz's research suggested an integrated system between the concepts of knowledge and human action, so that it could be interpreted that science was influenced by the activities carried out by humans themselves in gaining knowledge.…”
Section: Resultsmentioning
confidence: 97%
“…It is supposed to help us to determine the right relations between different values of science and to understand that science is not an isolated thing, but a totality which is not just a sum of its parts. (Ekawati et al, 2018) The students' content analysis and science process skills of the experimental group (scien¬tific independence-based learning with inquiry model) and control group (direct learning model) differed quite remarkably. Broszkiewicz's research suggested an integrated system between the concepts of knowledge and human action, so that it could be interpreted that science was influenced by the activities carried out by humans themselves in gaining knowledge.…”
Section: Resultsmentioning
confidence: 97%
“…The application of the ethnoscience-based course review horay learning model has been found to affect both scientific process ability and understanding of cultural meaning at the same time, consistent with previous research findings. In this learning process, a problem, issue, or scientific phenomenon is identified using science process skills (Idris et al, 2022;Rosana et al, 2021), and new knowledge is imparted to encourage students to seek facts and concepts on their own (Ekawati et al, 2018). The practice of science process skills occurs during the process of observing, classifying (grouping), communicating, predicting, inferring (concluding), formulating hypotheses, interpreting (analyzing), controlling variables, as well as designing and conducting experiments (Elfeky et al, 2020;Ihsan et al, 2017;Setiawan & Sugiyanto, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to solve problems in daily life will be influenced by the students' process skills (Tanti, Kuswanto, & Wardhana, 2020). In the learning process, a problem, an issue, or a scientific phenomenon is identified using science process skills (Idris, Talib, & Razali, 2022;Rosana, Kadarisman, Purwanto, & Sari, 2021), and they are created to impart new knowledge and encourage students to look up facts and concepts on their own (Ekawati, Iswari, & Lisdiana, 2018). The practice of science process skills occurs during the process of observing, classifying (grouping), communicating, predicting, inferring (concluding), formulating hypotheses, interpreting (analyzing), controlling variables, and designing & conducting experiments (Elfeky, Masadeh, & Elbyaly, 2020;Ihsan, Jamal, & Salam, 2017;Setiawan & Sugiyanto, 2020).…”
Section: Introductionmentioning
confidence: 99%